2019
DOI: 10.3390/genes10090699
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction and Analysis of Gene Networks of Human Neurotransmitter Systems Reveal Genes with Contentious Manifestation for Anxiety, Depression, and Intellectual Disabilities

Abstract: Background: The study of the biological basis of anxiety, depression, and intellectual disabilities in humans is one of the most actual problems of modern neurophysiology. Of particular interest is the study of complex interactions between molecular genetic factors, electrophysiological properties of the nervous system, and the behavioral characteristics of people. The neurobiological understanding of neuropsychiatric disorders requires not only the identification of genes that play a role in the molecular mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…The frequency of occurrence of S and L alleles of 5 HTTLPR polymorphism in Caucasoid and Mongoloid samples revealed is consistent with wellknown patterns obtained by comparing Connection of 5-HTTLPR polymorphism with event-related potentials under the stop-signal paradigm different ethnic groups (see Esau et al, 2008;Noskova et al, 2008;Ivanov et al, 2019). It is well known that the L allele is more common in Caucasians, while the S allele is more common in Mongoloids.…”
Section: Discussionsupporting
confidence: 87%
“…The frequency of occurrence of S and L alleles of 5 HTTLPR polymorphism in Caucasoid and Mongoloid samples revealed is consistent with wellknown patterns obtained by comparing Connection of 5-HTTLPR polymorphism with event-related potentials under the stop-signal paradigm different ethnic groups (see Esau et al, 2008;Noskova et al, 2008;Ivanov et al, 2019). It is well known that the L allele is more common in Caucasians, while the S allele is more common in Mongoloids.…”
Section: Discussionsupporting
confidence: 87%
“…For example, a 2019 study that used gene networks, constructed by adding genes functionally related to genes from an initial set, suggested that there are hypothetical mechanisms for the realization of a "contentious" phenotype and these genes may be characterized by an ambiguous phenotypic manifestation. The study was based on the principle of an ambiguous phenotypic manifestation for the same polymorphisms in people from different populations or people exposed to different environmental influences [28]. Another study, conducted on rats and mice, demonstrated that the behavioral phenotype has been found to be significantly correlated with the expression of the neuropeptide arginine vasopressin (AVP) at the level of the hypothalamic paraventricular nucleus and contribute to hyper-anxiety and depression-like behavior and single-nucleotide polymorphisms (SNPs) in the regulation structures of the AVP gene represent the basis of the phenotypic phenomena [3].…”
Section: Discussionmentioning
confidence: 99%
“…Targeted sequencing of 164 genes was performed basing on this material. The genes were selected as a part of the gene network reconstruction and analysis according to the following factors: the presence of effects on neurological disease and the difference in expression in various ethnic groups shown in the literature [3]. Targeted sequencing libraries were prepared for these 164 genes and a new generation of high coverage sequencing was carried out on 820 subjects from six subject groups.…”
Section: Genetic Datamentioning
confidence: 99%
“…In this connection, most of the open databases, including EEG, genotyping data, and psychological surveys, do not take into account the regional specifics of the survey participants. However, there are also studies [2,3], according to which the associations between genetic and neurophysiological factors on the one hand, and the risk of mental disorders and psychological personality traits, on the other hand, are significantly modulated by climatic and ethnographic characteristics of people. The novelty of our database is that it contains the results of a survey of people from four regions (Siberian industrial city, rural areas of Western Siberia, the Republic of Tuva, and the Republic of Yakutia), which differ greatly both in climate and ethnic composition of the population.…”
Section: Introductionmentioning
confidence: 99%